China's belt and road initiative and regional perceptions of China. Issue 1 (January 2018) - O'Trakoun, John
Abstract China's growing outward investment in Asia-Pacific is motivated by the potential for economic gains, but could also affect regional geopolitical risk. Using survey data from 2005 to 2016, we show that an increase in Chinese FDI in a country improves respondents' perceptions of Chinese influence on their country. We also show that perceptions of China are correlated with future business confidence in Asia-Pacific countries. With China advancing plans for further regional investment, notably through the Belt and Road Initiative, the economic and business outlook for Asia-Pacific could improve significantly, adding to existing advantages from regional economic and demographic trends.